2020
DOI: 10.1111/bjh.16616
|View full text |Cite
|
Sign up to set email alerts
|

At three years, patients with acute lymphoblastic leukaemia are still at risk for relapse. Results of the international MRC UKALLXII/ECOG E2993 trial

Abstract: Late relapse [>3 years from complete remission (CR)] in acute lymphoblastic leukaemia (ALL), is unusual. Data from the MRC UKALLXII/ECOG E2993 trial are presented to evaluate the incidence and characteristics of late relapse in adult ALL. Of 1,909 patients, 1,752 (92%) achieved CR and among these 757 (43Á2%) relapsed; 691 (91Á3%) within three years and 66 (8Á7%) beyond. Among these 66 patients, median time to relapse was 47 (37-144) months. Relapse beyond three years occurred in 3Á8% of all who achieved CR. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 30 publications
(33 reference statements)
2
10
0
Order By: Relevance
“…Acute lymphoblastic leukemia (ALL) often relapse early after the treatment course, within the first two years from the initial diagnosis [ 1 3 ]. Cases of late relapse (LR) occurring in ≥5 years from initial diagnosis have been reported infrequently [ 4 – 6 ]. However, there is no exact definition for late/very late relapse of ALL.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Acute lymphoblastic leukemia (ALL) often relapse early after the treatment course, within the first two years from the initial diagnosis [ 1 3 ]. Cases of late relapse (LR) occurring in ≥5 years from initial diagnosis have been reported infrequently [ 4 – 6 ]. However, there is no exact definition for late/very late relapse of ALL.…”
mentioning
confidence: 99%
“…Vora et al, reported 12 cases (~1%) with very-late relapse (VLR), defined as >10 years from the time of complete remission (CR), among 1134 children treated on the Medical Research Council (MRC) ALL trials [ 5 ]. The MRC UKALLXII/ECOG E2993 reported that 2.8% ( n = 21) of all relapses in adult ALL patients were late (≥5 years from remission) [ 6 ]. Rizzari et al showed that LR ALL (≥5 years) occurred in 2.9% of Italian children, with a median onset of 6.1 years (range: 5.8–13.7) [ 4 ].…”
mentioning
confidence: 99%
“…Hematologic malignancies account for 6–10% of all cancers and encompass a large group of blood neoplasms including different types of lymphoma, multiple myeloma, as well as myeloid and lymphoid leukemia [ 50 , 187 ]. The prognosis in this heterogeneous group of diseases ranges from nearly 90% overall survival rates in acute promyelocytic leukemia [ 188 ] to less than 6% after early relapse of acute lymphoblastic leukemia [ 189 ]. While there are certain recurrent genetic mutations in leukemia, hematologic malignancies remain largely heterogenic.…”
Section: Hematologic Malignanciesmentioning
confidence: 99%
“…Patients with acute lymphoblastic leukaemia (ALL), characterized by the monoclonal proliferation of immature cells in the lymphoid lineage, 1 often respond to the induction chemotherapies and >80% of adult ALL patients can achieve complete haematological response (CR). 2 However, the relapse rate ranges from 44% to 50% after the initial remission status, [3][4][5] and this is related to non-optimal overall survival (OS). [6][7][8] One of the treatment options for such chemotherapyrefractory or relapsed (r/r) ALL is allogeneic haematopoietic stem cell transplantation (allo-HSCT).…”
Section: Introductionmentioning
confidence: 99%